Media psychology - Brewer, Gayle, 1978- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'This edited textbook brings together broad and cutting-edge coverage of the core areas in media psychology for undergraduate, introductory-level students. Covering persuasion and influence, interaction with the media, and representation, the authors draw on specific campaigns and studies to introduce readers to key issues in this fascinating field'--
Includes bibliographical references and index.
Keywords: Mass media -- Psychological aspects